Design of the Cassava Slicing Machine Using the Pahl & Beitz Method (Case Study on a Chips MSME in Wonosobo, Central Java) - Catur Rizki Nugroho; Hasti Hasanati Marfuah (Institut Teknologi Dirgantara Adisutjipto, 2026)
The design of a cassava slicing machine using the Pahl & Beitz method serves as a solution to improve production capacity and work efficiency in a cassava chips MSME located in Wonosobo, Central Java. The manual cassava slicing process often requires a long time, increases the risk of injury, and produces non-uniform slices. The Pahl & Beitz method is applied through four main stages: task clarification, concept development, form design, and design evaluation. This study presents novelty in implementing a V-belt and pulley-based transmission system with a compact dimensional configuration adapted to the limited production space of MSMEs, as well as the use of type 304 stainless steel to ensure product hygiene and machine durability. Compared to conventional slicing machines, this design demonstrates an increase in capacity of up to 70 kg/hour, along with better energy efficiency and operator safety. This research is expected to serve as a reference for the development of appropriate technology to support MSMEs in the food processing sector, enhance competitiveness, and meet the growing market demand.